Family network of emerging Jewish intelligentsia (Cracow 1850-1918) - Minakowski, Marek Jerzy (Journal of Historical Network Research, 2018)
Mass genealogy of Jewish community in Cracow in 19th and early 20th century provides extraordinary opportunity to investigate the process of creating a new social class: society of traditional merchants and peddlers produced modern attorneys and doctors. Now we are able to capture the dynamics of the process. For many reasons, Jewish community in Cracow was an outstanding specimen. About 1900 there were about 25,000 Jews in Cracow (about 28% of city population). Almost whole family structure of the population has been discovered and analyzed as a continuous network. Over 1200 vertices have been identified as Jagiellonian University students between 1850 and 1918. We know what and when they were studying and often in which house they were born, what was their family social status etc. These data are used to model several key features of new social class emerging: what was the impact of father’s vs mother’s family on the choice of education and how the choice influenced further marriage. Especially interesting (sometimes counterintuitive) are results about influence of family status on whether such student finished his or her studies with doctoral diploma or dropped out without it.